Philip Schaff's concept of the church: with special reference to his role in the Mercersburg movement 1844 -1864 - Trost, Theodore L. (The University of Edinburgh, 1958)
Philip Schaff the Church historian and early advocate of Christian union is widely known, Philip Schaff the theologian, liturgist and co-leader of one of America's most significant theological movements, Cite Mercershurg movement, la leaser known. The purposes of thlc dissertation is to present Schaff's con¬ cept of the Church as expressed in his early works written during his pro¬ fessorship at the Mercersburg Seminary, and to describe his role in the con¬ troversy which marred the harmony of the German Reformed Church in the United States during most of the last century.

As In Schaff's day, so in ours, we too are concerned with the doctrine of the Church. Thus, this study is relevant not only to the current theological discussions between the Evangelical and Reformed Church and the Congregational Christian Churches who, in 1937, organically merged to form the United Church of Christ in America, but it also impinges upon the important issues underlying the 'church question' which is currently being debated by the members of the World Council of Churches. In this sense, we can say that the subject matter of this dissertation is relevant to the whole ecumenical movement. While not suggesting that we can live in the twentieth century with a nineteenth century outlook, it is nevertheless the conviction of the writer that the voice of Philip Schaff has much to say to those of a later generation, who, lire Schaff, also look forward to the time when "they all shall be one."